Evaluation of thyroid dysfunction in patients with menstrual disorders of reproductive age group: a prospective cross-sectional study - Kumari, Anupma; Rohatgi, Renu; Singh, Amrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Thyroid disorders specifically the hypothyroidism has been associated with menstrual disturbances in women of reproductive age group. The objective of this study was to estimate the prevalence of thyroid dysfunction and its correlation with menstrual disorders in women of reproductive age group. Methods: A hospital based prospective analytical study was carried out in the department of Obstetrics and Gynaecology of Nalanda Medical College and Hospital, Patna from March 2017 to March 2018. 56 women of reproductive age group between 18 to 45 years presenting with menstrual disorders (like menorrhagia, oligo/hypomenorrhea, polymenorrhea, metrorrhagia, and amenorrhea) were recruited in this study. Thyroid function test was done in all patients. Statistical analysis done. Results: Maximum number of patients were seen in the age group of 31-40 years. Most common menstrual complain was menorrhagia (46.42%) followed by hypo/oligomenorrhoea (17.86%). In patients with menstrual disorders, 41.07 % had thyroid disorders in which subclinical hypothyroidism was prevalent in 17.86%, overt hypothyroidism in 12.5%, and overt hyperthyroidism in 5.35% of the women. Menorrhagia was the commonest menstrual disorder (52.94%) seen in hypothyroid patients followed by polymenorrhoea. A high degree positive correlation was observed between thyroid dysfunction and menstrual disorder (Pearson correlation coefficient, r=0.93). Conclusions: Our study concluded that thyroid dysfunction should be considered as an important etiological factor for menstrual irregularity. Thus, thyroid function tests should be performed in all patients with menstrual irregularities to avoid unnecessary interventions like curettage and hysterectomy.